2017
DOI: 10.1136/bmjopen-2016-015666
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between receipt of substitutable for-fee vaccines and completion of the expanded programme on immunisation: a cross-sectional study in Fujian, China

Abstract: ObjectiveThe aim of this study was to evaluate the relationship between receipt of the substitutable-for-fee vaccines (SFV) and completion of the expanded programme on immunisation (EPI).Design and settingsA cross-sectional study was conducted in Fujian province, China.ParticipantsChildren who were born from 1 September 2009 to 31 August 2011, and who had been residing in the township for at least 3 months, were randomly recruited from 34 townships.Main outcomes measuresOutcomes were completion rate of the EPI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…China has now expanded NIP (including one dose of Bacille Calmette-Guerin vaccine, four doses of the oral live attenuated polio vaccine, etc.) and NIP vaccination rates have reached high levels ( 12 ). On the contrary, although non-NIP vaccines play an important role as a supplement or limited alternative to NIP in controlling the corresponding infectious diseases and meeting the health needs of different populations, the voluntary and out-of-pocket nature of non-NIP results in a low vaccination rate ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…China has now expanded NIP (including one dose of Bacille Calmette-Guerin vaccine, four doses of the oral live attenuated polio vaccine, etc.) and NIP vaccination rates have reached high levels ( 12 ). On the contrary, although non-NIP vaccines play an important role as a supplement or limited alternative to NIP in controlling the corresponding infectious diseases and meeting the health needs of different populations, the voluntary and out-of-pocket nature of non-NIP results in a low vaccination rate ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are still some barriers in improving the coverage and effectiveness of hepatitis B vaccination, such as a delay of the hepatitis B vaccine first dose, the impact of substitutable vaccine, immune failure, and cost of maternal antiviral treatment. 16–19 , 20 , 21 , 22 , 23 In addition, the decline in hepatitis B awareness is one of the challenges for the prevention and control of HBV infection in China. 16 , 24 In the present study, we identified that hepatitis B awareness has declined since the inclusion of hepatitis B into the national immunization program in 1992.…”
Section: Discussionmentioning
confidence: 99%
“…Followed by "False belief regarding vaccination and cultural barriers" also mentioned by 25% (9) of studies and similarly "Cost of vaccine and unavailability of the vaccine" mentioned by 25% ( 9) of reviewed studies. The fourth most mentioned barrier is "low awareness among providers and Inadequate knowledge of HBV among health-care workers" which mentioned by 19% ( 7 1, (Butsashvili et al, 2012;Giles-Vernick et al, 2016b;Larcher et al, 2001b); 2, (Cox et al, 2012b;Fourn et al, 2009b;Ritvo et al, 2003); 3, (Butsashvili et al, 2012;Ko et al, 2017b); 4, (Branco et al, 2014;Wu et al, 2017); 5, (Han et al, 2014); 6, (Bowman et al, 2014;MacDougall et al, 2015b); 7, (Han et al, 2014;Philbin et al, 2012b);8, (Philbin et al, 2012b); 9, (Akibu et al, 2018;Butsashvili et al, 2012;Harris et al, 2007); 10, (Juon et al, 2009b;Khan & Ross, 2013;Yau et al, 2016b;Zacharias et al, 2015); 11, (Butsashvili et al, 2012;MacDougall et al, 2015b); 12, (Navarro et al, 2014); 13, (Akibu et al, 2018;MacDougall et al, 2015b;Mollema et al, 2012); 14, (Chingle et al, 2017); 15, (Akibu et al, 2018;Branco et al, 2014); 16, (Butsashvili et al, 2012;MacDougall et al, 2015b;Philbin et al, 2012b); 17, (Kabir et al, 2010); 18, (Harris et al, 2007); 19, (Han et al, 2014); 20, (Ganczak et al, 2015;…”
Section: Barriers To Utilization Of Hepatitis B Vaccinementioning
confidence: 99%